Comparing smash performance and technique between elite male and female international players - Harley Towler; Mark King (2023)
Performance of the badminton smash plays a crucial role in success during competition. Differences in performance and technique between genders is of interest to players/coaches with respect to appropriate training intensity and understanding performance expectations during competition. Three-dimensional position data were collected for 26 male and 26 female elite international badminton players (world ranking: male = 59 ± 36, female = 54 ± 24) performing the smash. Male players compared to female players performed smashes with greater shuttlecock speed (98.7 vs 78.5 m×s-1; p < 0.001), racket head speed (63.3 vs. 51.0; p < 0.001), and shuttlecock angle below the horizontal (13.3° vs. 7.3°; p < 0.001) with the latter likely due to higher contact heights (2.90 vs 2.46 m; p < 0.001) and jump heights (53.6 vs 14.5 cm; p < 0.001). Female players typically used a ‘kick-through’ rather than a ‘two-footed jump’ movement. The majority of differences in technique, assessed via statistical parametric mapping, occurred during the backswing phase, where male players adopted a more flexed, less laterally flexed (to non-racket-arm side) and counter-rotated trunk positions. Male players held their racket arm further back during the backswing (negative shoulder plane of elevation angle), and the elbow joint was held in a more extended position at the start of the backswing and in a more flexed position just prior to contact. No differences were found at the wrist joint. This study provides normative performance and technique data for elite male and female international players, highlighting current differences between genders which may inform training and competition preparation.